Absolute bioavailability of microdosed midazolam after buccal administration is dependent on buccal exposure time - Grass, Jana; Rose, Peter; Burhenne, Jürgen; Blank, Antje; Haefeli, Walter E.; Mikus, Gerd (Journal of clinical pharmacology, 2021)
Midazolam is an established probe drug to assess cytochrome P450 3A activity (phenotyping). Microdosed midazolam is increasingly used for this purpose; a buccal formulation might be of advantage, but buccal absorption might occur. We therefore tested in a single-center, open-label clinical trial with 12 healthy volunteers the absolute bioavailability of 10 μg of midazolam after buccal administration in relation to buccal exposure time. In relation to a drinking solution, there was an increase of midazolam exposure (area under the plasma concentration-time curve from time 0 to infinity) with increasing buccal exposure time with an apparent saturation at 100-second buccal exposure. Absolute bioavailability increased from 27.8% (95% confidence interval, 23.5-32.9) for the drinking solution (0 seconds) to 66.1% (95% confidence interval, 60.0-72.8) after 100-second buccal exposure with no further increase after 150 seconds. A Hill equation described the time dependency of midazolam bioavailability with maximal bioavailability as 64.5% and buccal exposure time resulting in half maximal bioavailability increase as 16 seconds. In conclusion, midazolam bioavailability is highly dependent on buccal exposure time, and even a few seconds of buccal exposure will increase bioavailability due to buccal absorption. This needs to be taken into account for any buccal administration of midazolam.